VD_FINDINFO HC / 2021 / 197 vom 26. März 2020 - VD Tribunal cantonal (2020)
OBLIGATION D'ENTRETIEN, PROTECTION DE L'UNION CONJUGALE, DÉBUT, REVENU HYPOTHÉTIQUE | 163 CC, 175 CC, 176 al. 1 ch. 1 CC, 317 al. 1 CPC (CH)